Review on Artificial Intelligence and its Implementations in Digital Era (Journal of Information Technology and Digital World, 2022)
Artificial Intelligence (AI) moderns the present society and opens the door for many applications to boom digitally. AI plays a key role in the field of agriculture to space science. The development on cloud storage and wireless communication systems are assisting the AI to reach certain goals in the digital world. Also the improvements made to the electronic processors and other chips are helping the AI to gain its computational efficiency. The design of micro electronic devices are opening the possibility of moving the sensors to keep in distinguished locations though Internet of Things (IoT) communication. The objective of the paper is to review the performances of AI methodologies in various applications for identifying the research gaps.
Keywords: Neural networks; machine learning; deep learning; internet of things; cloud computing